High-strength bio-based aramid fiber, preparation method thereof and aramid cloth
By mixing and spinning the modified polyaramid concentrated solution and modified biobased microspheres, high-strength biobased aramid fibers were prepared, which solved the problem of performance degradation of existing fibers in harsh environments and achieved higher anti-aging, mechanical properties and flame retardant properties.
Patent Information
- Application Number
- CN202510424295.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In outdoor and high-risk environments, existing aramid fibers will gradually degrade under long-term exposure to environmental conditions such as ultraviolet rays, high temperatures, and humidity changes, which will affect the effectiveness and safety of use.
High-strength bio-based aramid fibers were prepared by mixing and spinning the modified polyaramid solution and modified bio-based microspheres. The modification process includes demethylation of sodium lignin sulfonate, grafting diethanolamine, reaction with epoxychlorohydrin and diethyl [2-(indole-3-yl)-2-oxoethyl]phosphate to form modified bio-based microspheres.
It improves the anti-aging, mechanical properties and flame retardant properties of high-strength bio-based aramid fiber, while enhancing its antibacterial properties and extending the service life of the fiber in harsh environments.
Smart Images

Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the field of aramid fibers, in particular to high-strength bio-based aramid fibers and a preparation method thereof, and aramid cloth. Background Art
[0002] Aramid fiber is a high-performance fiber material that shows great application potential in many fields with its excellent mechanical properties, light weight and high strength characteristics. Especially in the fields of protective materials, composite materials, aerospace, automotive industry, sporting goods and military equipment. Among them, aramid cloth, as an important derivative product, is widely used in bulletproof vests, helmets, aerospace materials and high-performance tires due to its excellent wear resistance, high temperature resistance and impact resistance. Although aramid fiber has many advantages, in actual applications, especially in outdoor and high-risk environments, its performance will gradually degrade under long-term exposure to environmental conditions such as ultraviolet rays, high temperature, and humidity changes, affecting the use effect and safety of use. Therefore, the present invention prepares a high-strength bio-based aramid fiber with excellent aging resistance. Summary of the invention
[0003] The object of the present invention is to provide a high-strength bio-based aramid fiber and a preparation method thereof and an aramid cloth to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-strength bio-based aramid fiber, wherein the high-strength bio-based aramid fiber is obtained by spinning a modified polyaramid concentrated solution and modified bio-based microspheres.
[0005] As an optimization, the modified polyaramid concentrated solution is prepared by reacting p-phenylenediamine, diamine monomer and terephthaloyl chloride.
[0006] As an optimization, the diamine monomer is prepared by reacting 2,6-diaminopyrazine and 5-nitroindazole carboxaldehyde.
[0007] As an optimization, the modified bio-based microspheres are obtained by demethylating sodium lignin sulfonate, grafting diethanolamine, and then reacting with epichlorohydrin and diethyl [2-(indol-3-yl)-2-oxoethyl] phosphate.
[0008] As an optimization, the sodium lignin sulfonate model is MN-2, which comes from Shenyang Xingzhenghe Chemical Co., Ltd.
[0009] A method for preparing high-strength bio-based aramid fiber, comprising the following preparation steps: (1) Sodium lignin sulfonate, anhydrous sodium sulfite and 2%-4% sodium hydroxide aqueous solution are mixed in a mass ratio of 1:(1-3):(10-20), ultrasonically treated at 35-45°C for 40-50 min, heated to 90-100°C, stirred at 100-200 rpm for 1-3 h, cooled naturally to room temperature, added with 1-3 mol / L hydrochloric acid solution to adjust the pH to 1-2, centrifuged and filtered, washed with deionized water for 3-5 times, and dried at 45-55°C for 11-13 h to obtain demethylated lignin; (2) Mix demethylated lignin, sodium hydroxide, diethanolamine and deionized water in a mass ratio of 1: (0.04-0.06): (0.2-0.4): (2-3), add 0.4-0.5 times the mass of demethylated lignin and a 35%-37% formaldehyde aqueous solution at a constant rate within 55-65 min at 80-90°C, reflux for 3-5 h, cool naturally to room temperature, add 0.9-1.1 mol / L hydrochloric acid solution dropwise until the precipitate remains unchanged in mass, filter, wash with isopropanol and petroleum ether for 3-5 times respectively, dry at 60-70°C for 11-13 h, grind and sieve 200-300 mesh, wash with deionized water for 3-5 times, and dry at 55-65°C for 23-25 h to obtain pre-modified lignin; (3) Pre-modified lignin, epichlorohydrin, anhydrous ethanol, and 0.9-1.1 mol / L sodium hydroxide solution were mixed in a mass ratio of 1: (0.1-0.2): (0.05-0.06): (1-3), and 0.05-0.06 times the mass of pre-modified lignin and 4-6 times the mass of pre-modified lignin were added. The mixture was heated to 85-95°C at 35-45°C and 200-300 rpm, and 0.3-0.5 times the mass of pre-modified lignin [2-( [indol-3-yl)-2-oxoethyl] diethyl phosphate, continue stirring for 1~3h, add 150~250μL of 45%~55% sodium hydroxide solution every 4~6min within 20~30min, continue stirring for 1~3h, remove the upper oil phase after standing and stratification, wash with petroleum ether and deionized water for 3~5 times respectively, and then wash with 0.1~0.3mol / L silver nitrate solution for 3~5 times, freeze-dry at -15~-5℃ for 47~49h to obtain modified bio-based microspheres; (4) 5-nitroindazole carboxaldehyde, 2,6-diaminopyrazine, acetic acid and methanol were mixed in a mass ratio of 1: (0.27-0.29): (0.29-0.33): (68-70), refluxed at 60-70°C for 7-9 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for 3-5 times respectively, and dried at 55-65°C for 11-13 hours to obtain dinitro monomer; dinitro monomer, 10% Palladium carbon and N-methylpyrrolidone are mixed in a mass ratio of 1: (0.06-0.08): (9-11), stirred in a hydrogen atmosphere at 20-30°C and 100-200 rpm for 23-25 hours, and then filtered. The filtrate is poured into deionized water with a mass of 90-110 times that of the dinitro monomer, allowed to stand for 1-3 hours, and then filtered. The mixture is washed with deionized water for 3-5 times, and dried at 60-70°C for 11-13 hours to obtain a diamine monomer. (5) N-methylpyrrolidone and deionized water are mixed in a volume ratio of 1:(3-5) to obtain a coagulation bath; p-phenylenediamine, diamine monomer, lithium chloride, pyridine and N-methylpyrrolidone are mixed in a mass ratio of 1:(3.3-3.4):(0.03-0.05):(0.01-0.03):(46-47), stirred in a nitrogen atmosphere at 45-55°C and 100-200 rpm for 20-30 min, terephthaloyl chloride (3.1-3.2 times the mass of p-phenylenediamine) is added, stirred at 5-15°C for 1-2 h, and then filtered to obtain a modified polyaramid concentrated solution; (6) The modified polyaramid concentrated solution and the modified bio-based microspheres are mixed in a mass ratio of 1:(0.03~0.05), and ultrasonically degassed at -1~1°C for 1~3 hours to obtain a spinning solution; the spinning solution is spun in a coagulation bath under the following conditions: a slurry temperature of 45~55°C, 0.3~0.5MPa, a coagulation bath temperature of 20~60°C, a spinneret draft ratio of -0.20~0 times, a hot water bath temperature of 75~85°C, a hot water bath stretching multiple of 1.3~1.8 times, and a spinneret specification of 45~55 holes to obtain spun fibers; the spun fibers are ultrasonically treated in a 0.2~0.4 mol / L zinc chloride solution for 1~2 hours, taken out, washed with deionized water for 3~5 times, and dried at 55~65°C for 11~13 hours to obtain high-strength bio-based aramid fibers.
[0010] As an optimization, the reaction equation of the pre-modified lignin in step (2) is: .
[0011] As an optimization, the reaction equation for modifying the bio-based microspheres in step (3) is: .
[0012] As an optimization, the liquid paraffin in step (3) is of industrial grade and comes from Henan Mingzhixin Chemical Products Co., Ltd.
[0013] As an optimization, the reaction equation of the diamine monomer in step (4) is: .
[0014] As an optimization, the 10% palladium carbon in step (4) comes from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0015] As an optimization, the reaction equation of the modified polyaramid concentrated solution in step (5) is: .
[0016] Aramid cloth is woven from the high-strength bio-based aramid fiber or the high-strength bio-based aramid fiber prepared by the preparation method of the high-strength bio-based aramid fiber.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: when preparing high-strength bio-based aramid fiber, the present invention demethylates sodium lignin sulfonate and then grafts diethanolamine, and then reacts with epichlorohydrin and [2-(indol-3-yl)-2-oxoethyl] diethyl phosphate to obtain modified bio-based microspheres; 2,6-diaminopyrazine and 5-nitroindazole formaldehyde are reacted to obtain a diamine monomer; p-phenylenediamine, the diamine monomer and terephthaloyl chloride are reacted to obtain a modified polyaramid concentrated solution; the modified polyaramid concentrated solution and the modified bio-based microspheres are mixed and spun to obtain the high-strength bio-based aramid fiber.
[0018] Firstly, sodium lignin sulfonate is demethylated and then grafted with diethanolamine, which is then reacted with epichlorohydrin and [2-(indol-3-yl)-2-oxoethyl] diethyl phosphate to obtain modified bio-based microspheres; sodium hydroxide is used to provide hydroxide ions, which undergo elimination reactions with methyl side chains in lignin molecules to remove methane gas, increase the content of phenolic hydroxyl groups on lignin, enhance the ability to capture free radicals, and improve the anti-aging properties of high-strength bio-based aramid fibers; diethanolamine is grafted through the Mannich reaction to increase the reactive sites, which are cross-linked with epichlorohydrin to form Microspheres, adding [2-(indol-3-yl)-2-oxoethyl] diethyl phosphate in the later stage of the reaction, increasing the esterification cross-linking network, improving the strength of the bio-based microspheres, and at the same time, the phosphorus element can promote the formation of the carbon layer and isolate oxygen during the combustion process, thereby enhancing the mechanical properties and flame retardant properties of the high-strength bio-based aramid fiber; using silver nitrate solution for washing, the sodium ions in the sodium lignin sulfonate are replaced by silver ions, which can affect the basic structures of bacterial cell walls, membranes, and nucleic acids, inhibit and kill bacteria, and improve the antibacterial properties of the high-strength bio-based aramid fiber.
[0019] Secondly, 2,6-diaminopyrazine and 5-nitroindazole formaldehyde are reacted to obtain a diamine monomer; p-phenylenediamine, diamine monomer and terephthaloyl chloride are reacted to obtain a modified polyaramid concentrated solution; the modified polyaramid concentrated solution and modified bio-based microspheres are mixed and spun to obtain high-strength bio-based aramid fibers; a diamine monomer containing an indazole conjugated ring and a carbon-nitrogen double bond is obtained by a Schiff base reaction and participates in the polymerization of the aramid main chain. The introduced indazole nitrogen heterocycle can form a coordinated crosslink with a complex metal ion, thereby improving the mechanical properties of the high-strength bio-based aramid fiber; At the same time, the carbon-nitrogen double bond can absorb ultraviolet rays of a specific wavelength, and can also cooperate with pyrazine and indazole nitrogen heterocycles to enhance the ability to complex metal ions, further improving the anti-aging and mechanical properties of high-strength bio-based aramid fibers; by impregnation with zinc chloride solution, metal ion coordination crosslinking is formed between the indole ring on the modified bio-based microspheres and the nitrogen heterocycle on the modified polyaramid, thereby improving the mechanical properties of the high-strength bio-based aramid fibers; at the same time, zinc ions can also destroy cell membrane structures, inhibit enzyme activity, and enhance the antibacterial properties of high-strength bio-based aramid fibers. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] The raw materials used in the following examples and comparative examples are all commercially available: the sodium lignin sulfonate model is MN-2, from Shenyang Xingzhenghe Chemical Co., Ltd.; the liquid paraffin model is industrial grade, from Henan Mingzhixin Chemical Products Co., Ltd.; the 10% palladium carbon is from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0022] Example 1 A method for preparing high-strength bio-based aramid fiber, the method for preparing high-strength bio-based aramid fiber comprising the following preparation steps: (1) Sodium lignin sulfonate, anhydrous sodium sulfite and 2% sodium hydroxide aqueous solution were mixed in a mass ratio of 1:1:10, ultrasonicated at 35°C for 50 min, heated to 90°C, stirred at 100 rpm for 3 h, cooled naturally to room temperature, added 1 mol / L hydrochloric acid solution to adjust the pH to 1, centrifuged and filtered, washed with deionized water for 3 times, and dried at 45°C for 13 h to obtain demethylated lignin; (2) Demethylated lignin, sodium hydroxide, diethanolamine and deionized water were mixed in a mass ratio of 1:0.04:0.2:2, and a 35% formaldehyde aqueous solution (0.4 times the mass of the demethylated lignin) was added at a uniform rate at 80°C for 55 min. The mixture was refluxed for 5 h, cooled naturally to room temperature, and a 0.9 mol / L hydrochloric acid solution was added dropwise until the precipitate remained unchanged in mass. The precipitate was filtered, washed with isopropanol and petroleum ether for 3 times, dried at 60°C for 13 h, ground and sieved with 200 mesh, washed with deionized water for 3 times, and dried at 55°C for 25 h to obtain pre-modified lignin. (3) Pre-modified lignin, epichlorohydrin, anhydrous ethanol, and 0.9 mol / L sodium hydroxide solution were mixed in a mass ratio of 1:0.1:0.05:1, and 0.05 times the mass of the pre-modified lignin, 0.05 times the mass of Span-60 and 4 times the mass of the pre-modified lignin were added. The mixture was heated to 85°C at 35°C and 200 rpm, and 0.3 times the mass of the pre-modified lignin, diethyl [2-(indol-3-yl)-2-oxoethyl] phosphate, was added. The stirring was continued for 3 hours. Within 20 minutes, 150 μL of 45% sodium hydroxide solution was added every 6 minutes. The stirring was continued for 3 hours. After standing for stratification, the upper oil phase was removed, and the mixture was washed with petroleum ether and deionized water for 3 times respectively, and then washed with 0.1 mol / L silver nitrate solution for 3 times. The mixture was freeze-dried at -15°C for 49 hours to obtain modified bio-based microspheres. (4) 5-nitroindazole carboxaldehyde, 2,6-diaminopyrazine, acetic acid and methanol were mixed in a mass ratio of 1:0.27:0.29:68, refluxed at 60°C for 9 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for 3 times respectively, and dried at 55°C for 13 hours to obtain a dinitro monomer; dinitro monomer, 10% palladium carbon and N-methylpyrrolidone were mixed in a mass ratio of 1:0.06:9, stirred at 20°C and 100 rpm for 25 hours in a hydrogen atmosphere and filtered, the filtrate was poured into deionized water 90 times the mass of the dinitro monomer, allowed to stand for 1 hour and filtered, washed with deionized water 3 times, and dried at 60°C for 13 hours to obtain a diamine monomer; (5) N-methylpyrrolidone and deionized water were mixed in a volume ratio of 1:3 to obtain a coagulation bath; p-phenylenediamine, diamine monomer, lithium chloride, pyridine and N-methylpyrrolidone were mixed in a mass ratio of 1:3.3:0.03:0.01:46, stirred at 45°C and 100 rpm for 30 min in a nitrogen atmosphere, terephthaloyl chloride (3.1 times the mass of p-phenylenediamine) was added, stirred at 5°C for 2 h and then filtered to obtain a modified polyaramid concentrated solution; (6) The modified polyaramid concentrated solution and the modified bio-based microspheres were mixed in a mass ratio of 1:0.03, and ultrasonically degassed at -1°C for 3 h to obtain a spinning solution; the spinning solution was spun in a coagulation bath under the following conditions: a slurry temperature of 45°C, 0.3 MPa, a coagulation bath temperature of 20°C, a spinneret draft ratio of -0.20 times, a hot water bath temperature of 75°C, a hot water bath stretching multiple of 1.3 times, and a spinneret specification of 45 holes to obtain spun fibers; the spun fibers were ultrasonically treated in a 0.2 mol / L zinc chloride solution for 2 h, taken out, washed three times with deionized water, and dried at 55°C for 13 h to obtain high-strength bio-based aramid fibers.
[0023] Example 2 A method for preparing high-strength bio-based aramid fiber, the method for preparing high-strength bio-based aramid fiber comprising the following preparation steps: (1) Sodium lignin sulfonate, anhydrous sodium sulfite and 3% sodium hydroxide aqueous solution were mixed in a mass ratio of 1:2:15, ultrasonicated at 40°C for 45 min, heated to 95°C, stirred at 150 rpm for 2 h, cooled naturally to room temperature, added 2 mol / L hydrochloric acid solution to adjust the pH to 1.5, centrifuged and filtered, washed with deionized water for 4 times, and dried at 50°C for 12 h to obtain demethylated lignin; (2) Demethylated lignin, sodium hydroxide, diethanolamine and deionized water were mixed in a mass ratio of 1:0.05:0.3:2.5, and a 36% formaldehyde aqueous solution with a mass fraction of 0.45 times the mass of the demethylated lignin was added at a uniform rate at 85°C for 60 min, refluxed for 4 h, cooled naturally to room temperature, and 1 mol / L hydrochloric acid solution was added dropwise until the precipitate remained unchanged in mass. After that, it was filtered, washed with isopropanol and petroleum ether for 4 times respectively, dried at 65°C for 12 h, ground and sieved to 250 mesh, washed with deionized water for 4 times, and dried at 60°C for 24 h to obtain pre-modified lignin; (3) Pre-modified lignin, epichlorohydrin, anhydrous ethanol, and 1 mol / L sodium hydroxide solution were mixed in a mass ratio of 1:0.15:0.055:2, and 0.055 times the mass of the pre-modified lignin was added with Span-60 and 5 times the mass of the pre-modified lignin. The mixture was heated to 90°C at 40°C and 250 rpm, and 0.4 times the mass of the pre-modified lignin was added with diethyl [2-(indol-3-yl)-2-oxoethyl] phosphate. The mixture was stirred for 2 h. Within 25 min, 200 μL of 50% sodium hydroxide solution was added every 5 min. The mixture was stirred for 2 h. After standing for stratification, the upper oil phase was removed, and the mixture was washed with petroleum ether and deionized water for 4 times, respectively, and then washed with 0.2 mol / L silver nitrate solution for 4 times. The mixture was freeze-dried at -10°C for 48 h to obtain modified bio-based microspheres. (4) 5-nitroindazole carboxaldehyde, 2,6-diaminopyrazine, acetic acid and methanol were mixed in a mass ratio of 1:0.28:0.31:69, refluxed at 65°C for 8 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for 4 times respectively, and dried at 60°C for 12 hours to obtain a dinitro monomer; dinitro monomer, 10% palladium carbon and N-methylpyrrolidone were mixed in a mass ratio of 1:0.07:10, stirred at 25°C and 150rpm for 24 hours in a hydrogen atmosphere and filtered, the filtrate was poured into deionized water 100 times the mass of the dinitro monomer, allowed to stand for 2 hours and filtered, washed with deionized water 4 times, and dried at 65°C for 12 hours to obtain a diamine monomer; (5) N-methylpyrrolidone and deionized water were mixed in a volume ratio of 1:4 to obtain a coagulation bath; p-phenylenediamine, diamine monomer, lithium chloride, pyridine and N-methylpyrrolidone were mixed in a mass ratio of 1:3.35:0.04:0.02:46.5, stirred at 50°C and 150 rpm for 25 min in a nitrogen atmosphere, terephthaloyl chloride (3.15 times the mass of p-phenylenediamine) was added, stirred at 10°C for 1.5 h and then filtered to obtain a modified polyaramid concentrated solution; (6) The modified polyaramid concentrated solution and the modified bio-based microspheres were mixed in a mass ratio of 1:0.04, and ultrasonically degassed at 0°C for 2 h to obtain a spinning solution; the spinning solution was spun in a coagulation bath under the conditions of a nitrogen atmosphere, a slurry temperature of 50°C, 0.4 MPa, a coagulation bath temperature of 40°C, a spinneret draft ratio of -0.1 times, a hot water bath temperature of 80°C, a hot water bath stretching multiple of 1.5 times, and a spinneret specification of 50 holes to obtain spun fibers; the spun fibers were ultrasonically treated in a 0.3 mol / L zinc chloride solution for 1.5 h, taken out, washed 4 times with deionized water, and dried at 60°C for 12 h to obtain high-strength bio-based aramid fibers.
[0024] Example 3 A method for preparing high-strength bio-based aramid fiber, the method for preparing high-strength bio-based aramid fiber comprising the following preparation steps: (1) Sodium lignin sulfonate, anhydrous sodium sulfite and 4% sodium hydroxide aqueous solution were mixed in a mass ratio of 1:3:20, ultrasonicated at 45°C for 40 min, heated to 100°C, stirred at 200 rpm for 1 h, cooled naturally to room temperature, added 3 mol / L hydrochloric acid solution to adjust the pH to 2, centrifuged and filtered, washed with deionized water 5 times, and dried at 55°C for 11 h to obtain demethylated lignin; (2) Demethylated lignin, sodium hydroxide, diethanolamine and deionized water were mixed in a mass ratio of 1:0.06:0.4:3, and a 37% formaldehyde aqueous solution (0.5 times the mass of the demethylated lignin) was added at a uniform rate at 90°C for 65 min. The mixture was refluxed for 3 h, cooled naturally to room temperature, and a 1.1 mol / L hydrochloric acid solution was added dropwise until the precipitate remained unchanged in mass. The precipitate was then filtered, washed with isopropanol and petroleum ether for 5 times, dried at 70°C for 11 h, ground and sieved to 300 mesh, washed with deionized water for 5 times, and dried at 65°C for 23 h to obtain pre-modified lignin. (3) Pre-modified lignin, epichlorohydrin, anhydrous ethanol, and 1.1 mol / L sodium hydroxide solution were mixed in a mass ratio of 1:0.2:0.06:3, and 0.06 times the mass of pre-modified lignin was added with Span-60 and 6 times the mass of pre-modified lignin. The mixture was heated to 95°C at 45°C and 300 rpm, and 0.5 times the mass of pre-modified lignin was added with diethyl [2-(indol-3-yl)-2-oxoethyl] phosphate. The mixture was stirred for 1 hour. Within 30 minutes, 250 μL of 55% sodium hydroxide solution was added every 4 minutes. The mixture was stirred for 1 hour. After standing for stratification, the upper oil phase was removed, and the mixture was washed with petroleum ether and deionized water for 5 times, respectively, and then washed with 0.3 mol / L silver nitrate solution for 5 times. The mixture was freeze-dried at -5°C for 47 hours to obtain modified bio-based microspheres. (4) 5-nitroindazole carboxaldehyde, 2,6-diaminopyrazine, acetic acid and methanol were mixed in a mass ratio of 1:0.29:0.33:70, refluxed at 70°C for 7 hours, naturally cooled to room temperature and filtered, washed with methanol and deionized water for 5 times respectively, and dried at 65°C for 11 hours to obtain a dinitro monomer; dinitro monomer, 10% palladium carbon and N-methylpyrrolidone were mixed in a mass ratio of 1:0.08:11, stirred at 30°C and 200rpm in a hydrogen atmosphere for 23 hours and filtered, the filtrate was poured into deionized water 110 times the mass of the dinitro monomer, allowed to stand for 3 hours and filtered, washed with deionized water 5 times, and dried at 70°C for 11 hours to obtain a diamine monomer; (5) N-methylpyrrolidone and deionized water were mixed in a volume ratio of 1:5 to obtain a coagulation bath; p-phenylenediamine, diamine monomer, lithium chloride, pyridine and N-methylpyrrolidone were mixed in a mass ratio of 1:3.4:0.05:0.03:47, stirred for 20 min at 55°C and 200 rpm in a nitrogen atmosphere, 3.2 times the mass of p-phenylenediamine was added to terephthaloyl chloride, stirred at 15°C for 1 h and then filtered to obtain a modified polyaramid concentrated solution; (6) The modified polyaramid concentrated solution and the modified bio-based microspheres were mixed in a mass ratio of 1:0.05, and ultrasonically degassed at 1°C for 1 h to obtain a spinning solution; the spinning solution was spun in a coagulation bath under the conditions of a nitrogen atmosphere, a slurry temperature of 55°C, 0.5 MPa, a coagulation bath temperature of 60°C, a spinneret draft ratio of 0 times, a hot water bath temperature of 85°C, a hot water bath stretching multiple of 1.8 times, and a spinneret specification of 55 holes to obtain spun fibers; the spun fibers were ultrasonically treated in a 0.4 mol / L zinc chloride solution for 2 h, taken out, washed 5 times with deionized water, and dried at 65°C for 11 h to obtain high-strength bio-based aramid fibers.
[0025] Comparative Example 1: The preparation method of high-strength bio-based aramid fiber in Comparative Example 1 is different from that in Example 2 only in step (1), in which step (1) is omitted and sodium lignin sulfonate is not subjected to demethylation treatment. The remaining steps are the same as those in Example 2.
[0026] Comparative Example 2: The preparation method of high-strength bio-based aramid fiber in Comparative Example 2 differs from that in Example 2 only in step (3). Step (3) is modified as follows: pre-modified lignin, epichlorohydrin, anhydrous ethanol, and 1 mol / L sodium hydroxide solution are mixed in a mass ratio of 1:0.15:0.055:2, 0.055 times the mass of the pre-modified lignin of Span-60 and 5 times the mass of the pre-modified lignin of liquid paraffin are added, the mixture is heated to 90°C at 40°C and 250 rpm with stirring, 0.4 times the mass of the pre-modified lignin of diethyl [2-(indol-3-yl)-2-oxoethyl] phosphate is added, stirring is continued for 2 h, 200 μL of 50% sodium hydroxide solution is added every 5 min within 25 min, stirring is continued for 2 h, the upper oil phase is removed after standing for stratification, the mixture is washed 4 times with petroleum ether and deionized water respectively, and freeze-dried at -10°C for 48 h to obtain modified bio-based microspheres. The remaining steps are the same as in Example 2.
[0027] Comparative Example 3: The preparation method of high-strength bio-based aramid fiber in Comparative Example 3 is different from that in Example 2 only in step (3). Step (3) is modified as follows: pre-modified lignin, epichlorohydrin, anhydrous ethanol, and 1 mol / L sodium hydroxide solution are mixed in a mass ratio of 1:0.15:0.055:2, 0.055 times the mass of pre-modified lignin, Span-60 and 5 times the mass of pre-modified lignin are added, the temperature is raised to 90°C at 40°C and 250 rpm, 200 μL of 50% sodium hydroxide solution is added every 5 minutes within 25 minutes, stirring is continued for 2 hours, the upper oil phase is removed after standing and stratification, and the microspheres are washed with petroleum ether and deionized water for 4 times respectively, and then washed with 0.2 mol / L silver nitrate solution for 4 times, and freeze-dried at -10°C for 48 hours to obtain modified bio-based microspheres. The remaining steps are the same as those in Example 2.
[0028] Comparative Example 4: The preparation method of high-strength bio-based aramid fiber in Comparative Example 4 differs from that in Example 2 only in steps (4) and (5). Step (4) is omitted, and step (5) is modified as follows: N-methylpyrrolidone and deionized water are mixed at a volume ratio of 1:4 to obtain a coagulation bath; p-phenylenediamine, lithium chloride, pyridine and N-methylpyrrolidone are mixed at a mass ratio of 1:0.04:0.02:46.5, stirred at 50°C and 150 rpm for 25 min in a nitrogen atmosphere, terephthaloyl chloride with a mass of 1.9 times that of p-phenylenediamine is added, stirred at 10°C for 1.5 h, and filtered to obtain a modified polyaramid concentrated solution. The remaining steps are the same as those in Example 2.
[0029] Comparative Example 5: The preparation method of high-strength bio-based aramid fiber in Comparative Example 5 is different from that in Example 2 only in step (6), and step (6) is modified as follows: the modified polyaramid concentrated solution and the modified bio-based microspheres are mixed at a mass ratio of 1:0.04, and ultrasonically degassed at 0°C for 2 hours to obtain a spinning solution; the spinning solution is spun in a coagulation bath under the conditions of a nitrogen atmosphere, a slurry temperature of 50°C, 0.4MPa, a coagulation bath temperature of 40°C, a spinneret draft ratio of -0.1 times, a hot water bath temperature of 80°C, a hot water bath stretching multiple of 1.5 times, and a spinneret specification of 50 holes, and the spinning solution is taken out, washed with deionized water 4 times, and dried at 60°C for 12 hours to obtain a high-strength bio-based aramid fiber. The remaining steps are the same as those in Example 2.
[0030] Test Case 1. Mechanical properties Test method: The high-strength bio-based aramid fibers obtained in each embodiment and comparative example were tested for 25 mm single-filament breaking strength N using an XQ-1A fiber strength tester under the conditions of a pretension of 0.03 cN / dtex, a clamp distance of 20 mm, a tensile speed of 10 mm / min, and a lower clamp descending speed of 10 mm / min.0; 2. Anti-aging Test method: The high-strength bio-based aramid fibers obtained in each embodiment and comparative example were placed in a light-oxidation aging test chamber, and a high-pressure mercury lamp was used as the light source for artificial accelerated ultraviolet aging experiments. The ultraviolet irradiation intensity on the sample surface was 2200 µw / cm 2 , aging temperature is 45℃, aging time is 48h. Measure the breaking strength N1, calculate the aging rate = (N0-N1) / N0*100%; 3. Antibacterial Test method: Take 0.5g of the high-strength bio-based aramid fiber obtained in each embodiment and comparative example, cut it into pieces, sterilize it with ultraviolet light to obtain the test sample, and mix the test sample, 100μL of live bacteria (1×10 6 The bacterial suspension of Staphylococcus aureus and 10mL PBS buffer were placed in a 30mL sample bottle and mixed, cultured at 37℃ for 24h, 15mL PBS buffer was added and shaken, 10 times diluted and 100μL was taken out and placed in broth medium, cultured at 37℃ for 24h, the colony count Q1 was measured (the blank control sample Q0 was used without adding sample), and the antibacterial rate was calculated as (Q0-Q1) / Q0*100%; 4. Flame retardancy Test method: The high-strength bio-based aramid fibers obtained in each example and comparative example were tested for limiting oxygen index according to GB / T2406.
[0031] Table 1 below shows the analysis results of the anti-aging, antibacterial, flame retardancy and mechanical properties of the high-strength bio-based aramid fibers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0032]
[0033] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the high-strength bio-based aramid fiber prepared in the present invention has good anti-aging, antibacterial, flame retardant and mechanical properties.
[0034] Comparative Example 1 did not perform demethylation modification on sodium lignin sulfonate; by comparison, the aging rates of Examples 1, 2, and 3 were lower than those of Comparative Example 1, indicating that sodium hydroxide was used to provide hydroxide ions, which reacted with the methyl side chains in the lignin molecules to remove methane gas, increase the content of phenolic hydroxyl groups on lignin, enhance the ability to capture free radicals, and improve the aging resistance of high-strength bio-based aramid fibers.
[0035] Comparative Example 2 did not replace the sodium ions on the sodium lignin sulfonate with silver ions; by comparison, the antibacterial rates of Examples 1, 2, and 3 were higher than those of Comparative Example 2, indicating that the sodium ions in the sodium lignin sulfonate were replaced with silver ions by washing with a silver nitrate solution, and that the silver ions could affect the basic structures of bacterial cell walls, membranes, and nucleic acids, inhibit and kill bacteria, and improve the antibacterial properties of the high-strength bio-based aramid fiber.
[0036] In Comparative Example 3, [2-(indol-3-yl)-2-oxoethyl] diethyl phosphate was not added when preparing the modified bio-based microspheres; by comparison, the limiting oxygen index and breaking strength of Examples 1, 2, and 3 are higher than those of Comparative Example 3, indicating that diethanolamine is grafted through the Mannich reaction to increase the reactive sites, and the microspheres are cross-linked with epichlorohydrin to form microspheres, and [2-(indol-3-yl)-2-oxoethyl] diethyl phosphate is added in the later stage of the reaction to increase the esterification cross-linking network and improve the strength of the bio-based microspheres. At the same time, phosphorus can promote the formation of a carbon layer and isolate oxygen during the combustion process, thereby enhancing the mechanical properties and flame retardant properties of the high-strength bio-based aramid fiber.
[0037] Comparative Example 4 does not graft a diamine monomer onto the polyaramid main chain; by comparison, Examples 1, 2, and 3 have higher aging rates and breaking strengths than those of Comparative Example 4, indicating that the diamine monomer containing an indazole conjugated ring and a carbon-nitrogen double bond is obtained by utilizing the Schiff base reaction, and participates in the polymerization of the aramid main chain, and the introduced indazole nitrogen heterocycle can complex metal ions and form coordination crosslinks, thereby improving the mechanical properties of the high-strength bio-based aramid fiber; at the same time, the carbon-nitrogen double bond can absorb ultraviolet rays of a specific wavelength, and can also cooperate with pyrazine and indazole nitrogen heterocycles to enhance the ability to complex metal ions, thereby further improving the aging resistance and mechanical properties of the high-strength bio-based aramid fiber.
[0038] In Comparative Example 5, the spun fibers were not impregnated with zinc chloride solution. By comparison, the antibacterial rates and breaking strengths of Examples 1, 2, and 3 were higher than those of Comparative Example 5, indicating that metal ion coordination crosslinking was formed between the indole ring on the modified bio-based microspheres and the nitrogen heterocyclic ring on the modified polyaramid through immersion in zinc chloride solution, thereby improving the mechanical properties of the high-strength bio-based aramid fibers. At the same time, zinc ions can also destroy the cell membrane structure, inhibit enzyme activity, and enhance the antibacterial properties of the high-strength bio-based aramid fibers.
[0039] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-strength bio-based aramid fiber, characterized in that: The high-strength bio-based aramid fiber is prepared by mixing and spinning a modified polyaramid concentrated solution and a modified bio-based microsphere; the modified polyaramid concentrated solution is obtained by reacting p-phenylenediamine, a diamine monomer and terephthaloyl chloride; the diamine monomer is obtained by reacting 2,6-diaminopyrazine and 5-nitroindazole formaldehyde; the modified bio-based microsphere is obtained by demethylating sodium lignin sulfonate, grafting diethanolamine, and then reacting with epichlorohydrin and diethyl [2-(indol-3-yl)-2-oxoethyl] phosphate.
2. A method for preparing high-strength bio-based aramid fiber, characterized in that: The method comprises the following preparation steps: (1) mixing sodium lignin sulfonate, anhydrous sodium sulfite and sodium hydroxide aqueous solution, dispersing by ultrasonication, heating to react, cooling to room temperature, adding hydrochloric acid to adjust the pH, washing and drying to obtain demethylated lignin; (2) Mix the demethylated lignin, sodium hydroxide, diethanolamine and deionized water, add formaldehyde aqueous solution, reflux reaction, cool to room temperature, add hydrochloric acid solution dropwise until the precipitate is precipitated with constant mass, filter, wash, dry, grind and sieve to obtain pre-modified lignin; (3) Pre-modified lignin, epichlorohydrin, anhydrous ethanol and sodium hydroxide solution are mixed, pre-span-60 and liquid paraffin are added, the mixture is stirred and heated, diethyl [2-(indol-3-yl)-2-oxoethyl] phosphate is added, the mixture is stirred continuously, sodium hydroxide solution is added, the oil phase is removed after standing and stratification, and the mixture is washed and freeze-dried to obtain modified bio-based microspheres; (4) Mix 5-nitroindazole carboxaldehyde, 2,6-diaminopyrazine, acetic acid and methanol, reflux, cool to room temperature, filter, wash and dry to obtain a dinitro monomer; mix the dinitro monomer, 10% palladium carbon and N-methylpyrrolidone, stir and filter in a hydrogen atmosphere, pour the filtrate into deionized water, let stand, wash and dry to obtain a diamine monomer; (5) N-methylpyrrolidone and deionized water are mixed to obtain a coagulation bath; p-phenylenediamine, diamine monomer, lithium chloride, pyridine and N-methylpyrrolidone are mixed, stirred in a nitrogen atmosphere, terephthaloyl chloride is added, stirred and filtered to obtain a modified polyaramid concentrated solution; (6) The modified polyaramid concentrated solution and the modified bio-based microspheres are mixed and ultrasonically degassed to obtain a spinning solution; the spinning solution is spun in a nitrogen atmosphere to obtain spun fibers; the spun fibers are ultrasonically treated in a zinc chloride solution, washed and dried to obtain high-strength bio-based aramid fibers.
3. The method for preparing high-strength bio-based aramid fiber according to claim 2, characterized in that: The preparation process of the demethylated lignin in step (1) is as follows: sodium lignin sulfonate, anhydrous sodium sulfite and a sodium hydroxide aqueous solution with a mass fraction of 2% to 4% are mixed in a mass ratio of 1: (1-3): (10-20), ultrasonicated at 35-45° C. for 40-50 min, heated to 90-100° C., stirred at 100-200 rpm for 1-3 h, naturally cooled to room temperature, added with 1-3 mol / L hydrochloric acid solution to adjust the pH to 1-2, and then centrifuged and filtered, washed with deionized water for 3-5 times, and dried at 45-55° C. for 11-13 h to obtain demethylated lignin.
4. The method for preparing high-strength bio-based aramid fiber according to claim 2, characterized in that: The preparation process of the pre-modified lignin in step (2) is as follows: demethylated lignin, sodium hydroxide, diethanolamine and deionized water are mixed in a mass ratio of 1: (0.04-0.06): (0.2-0.4): (2-3), and a 35%-37% formaldehyde aqueous solution with a mass fraction of 0.4-0.5 times the mass of the demethylated lignin is uniformly added at 80-90° C. and 55-65 min. The mixture is refluxed for 3-5 h, cooled naturally to room temperature, and a 0.9-1.1 mol / L hydrochloric acid solution is added dropwise until the precipitate is precipitated with a constant mass, and then filtered. The mixture is washed with isopropanol and petroleum ether for 3-5 times respectively, dried at 60-70° C. for 11-13 h, ground and sieved through 200-300 mesh, washed with deionized water for 3-5 times, and dried at 55-65° C. for 23-25 h to obtain the pre-modified lignin.
5. The method for preparing high-strength bio-based aramid fiber according to claim 2, characterized in that: The preparation process of the modified bio-based microspheres in step (3) is as follows: pre-modified lignin, epichlorohydrin, anhydrous ethanol, and 0.9-1.1 mol / L sodium hydroxide solution are mixed in a mass ratio of 1: (0.1-0.2): (0.05-0.06): (1-3), 0.05-0.06 times the mass of pre-modified lignin Span-60 and 4-6 times the mass of pre-modified lignin are added, the mixture is heated to 85-95°C at 35-45°C and 200-300 rpm, and 0.3- 0.5 times of [2-(indol-3-yl)-2-oxoethyl] diethyl phosphate, continue stirring for 1~3h, add 150~250μL of 45%~55% sodium hydroxide solution every 4~6min within 20~30min, continue stirring for 1~3h, let stand and stratify, remove the upper oil phase, wash with petroleum ether and deionized water for 3~5 times respectively, and then wash with 0.1~0.3mol / L silver nitrate solution for 3~5 times, freeze-dry at -15~-5℃ for 47~49h to obtain modified bio-based microspheres.
6. The method for preparing high-strength bio-based aramid fiber according to claim 2, characterized in that: The preparation process of the diamine monomer in step (4) is as follows: dinitro monomer, 10% palladium carbon and N-methylpyrrolidone are mixed in a mass ratio of 1: (0.06-0.08): (9-11), stirred in a hydrogen atmosphere at 20-30° C. and 100-200 rpm for 23-25 hours, and then filtered, the filtrate is poured into deionized water with a mass of 90-110 times that of the dinitro monomer, allowed to stand for 1-3 hours, and then filtered, washed with deionized water for 3-5 times, and dried at 60-70° C. 11~13h to obtain a diamine monomer; the preparation process of the nitro monomer is: 5-nitroindazole carboxaldehyde, 2,6-diaminopyrazine, acetic acid and methanol are mixed in a mass ratio of 1: (0.27~0.29): (0.29~0.33): (68~70), refluxed at 60~70℃ for 7~9h, naturally cooled to room temperature and then filtered, washed with methanol and deionized water for 3~5 times respectively, and dried at 55~65℃ for 11~13h to obtain a dinitro monomer.
7. The method for preparing high-strength bio-based aramid fiber according to claim 2, characterized in that: The preparation process of the modified polyaramid concentrated solution in step (5) is as follows: N-methylpyrrolidone and deionized water are mixed in a volume ratio of 1:(3-5) to obtain a coagulation bath; p-phenylenediamine, diamine monomer, lithium chloride, pyridine and N-methylpyrrolidone are mixed in a mass ratio of 1:(3.3-3.4):(0.03-0.05):(0.01-0.03):(46-47), stirred in a nitrogen atmosphere at 45-55° C. and 100-200 rpm for 20-30 min, terephthaloyl chloride (3.1-3.2 times the mass of p-phenylenediamine) is added, stirred at 5-15° C. for 1-2 h, and then filtered to obtain a modified polyaramid concentrated solution.
8. The method for preparing high-strength bio-based aramid fiber according to claim 2, characterized in that: The preparation process of the high-strength bio-based aramid fiber in step (6) is as follows: the spun fiber is ultrasonically treated in a 0.2-0.4 mol / L zinc chloride solution for 1-2 hours, then taken out, washed with deionized water for 3-5 times, and dried at 55-65°C for 11-13 hours to obtain the high-strength bio-based aramid fiber; the preparation process of the spun fiber is as follows: the spinning solution is placed in a nitrogen atmosphere, the slurry temperature is 45-55°C, 0.3-0.5 MPa, and the coagulation bath temperature is Spinning is carried out in a coagulation bath under the conditions of 20-60°C, spinneret draft ratio of -0.20-0 times, hot water bath temperature of 75-85°C, hot water bath stretching multiple of 1.3-1.8 times, and spinneret specification of 45-55 holes to obtain spun fibers; the preparation process of the spinning solution is as follows: the modified polyaramid concentrated solution and the modified bio-based microspheres are mixed in a mass ratio of 1: (0.03-0.05), and ultrasonic degassing is carried out at -1-1°C for 1-3 hours to obtain the spinning solution.
9. An aramid cloth, characterized in that: The high-strength bio-based aramid fiber is woven using the high-strength bio-based aramid fiber described in claim 1 or the high-strength bio-based aramid fiber prepared by the preparation method of the high-strength bio-based aramid fiber described in any one of claims 2 to 8.
Citation Information
Patent Citations
Method for preparing phosphorus-containing organosilicon flame retardant
CN101935399A
High-performance aromatic polymer fiber and preparation method
CN110130095A
Heterocyclic meta-aramid fiber and preparation method thereof
CN114606598A
Preparation method of micro-nano lignin-based wood glue reinforcing agent
CN117004041A
Lignin porous microspheres loaded with metal nanoparticles as well as preparation method and application of lignin porous microspheres
CN118179596A